The Curse of Flexibility Under Uncertainty - Engin Kara (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
How firms respond to uncertainty determines economic policy effectiveness. Using Brexit as a natural experiment, I document that flexible price-setters—those most responsive to monetary policy—paradoxically reduce adjustment more than sticky firms under uncertainty. This 'curse of flexibility' reverses menu cost models' foundational prediction that flexibility amplifies responses. Under uncertainty, resetting prices exposes firms to symmetric shocks, while maintaining current prices provides partial insulation. Flexible-price firms can afford to exploit this differential exposure by waiting; sticky-price firms cannot. This creates a policy challenge: uncertainty weakens monetary transmission when needed most, as flexible firms—the most responsive channel—become more cautious during crises.
Keywords: E31; D83; E52; D21; L11; 330; menu costs; price stickiness; uncertainty; state-dependent pricing; heterogeneous firms; monetary policy transmission